Peran Humas Dalam Meningkatkan Citra Positif Pada Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jawa Timur - Rakhmad Handin Setya Purwo; Durinta Puspasari (Universitas Negeri Surabaya, 2020)
Every agency or organization definitely needs a positive image or good among the public. A good image is a need of an agency or organization, so this is one of the tasks carried out by public relations through the programs carried out. Because the success gained by an agency is inseparable from public relations who are able to run its role well. For the sake of creating a positive image, public relations must be able to carry out its role properly, because BPSDM is an agency tasked with educating the state civil apparatus before carrying out duties according to his position. So here public relations must be able to create, build, improve and maintain the image of the organization among the public. Public relations has the obligation to develop a harmonious relationship with the public because this is a public relations activity to build a good relationship to create a good image. The purpose of this study was to analyze the role of public relations in enhancing a positive image in the government agency BPSDM East Java Province. This type of research is qualitative descriptive. The subjects of this study were 3 public relations staff. Data analysis here uses the Miles and Huberman models using source triangulation. The results of this study indicate that the role of BPSDM public relations in East Java Province namely as a communication facilitator, expert advisor, problem solving facilitator and communication technician has been going well.Keywords: positive image; public relations.